Improving student learning outcomes in the material of heat and its transfer through the social technology science model with a constructivist approach - Jayanta Nuniya (Journal of diversity in learning (JDIL), 2022)
Based on observations at the School and Center - Janodaya Vidhyalaya, Madanapalli, data was obtained that the use of appropriate learning models was not maximized, students still had difficulty understanding the material, lack of cooperation between students and the class seemed crowded. The research design used is classroom action research. The subjects of this study were students of class VII-I School and Center – Janodaya Vidhyalaya, Madanapalli in the even semester of the 2019/2020 academic year. The data taken in this study included attitudes and skills values taken using observation sheets, and knowledge values taken by evaluation questions. The results showed: (1) The results of the attitude assessment in cycle I amounted to 12.5% in the good category, while in cycle II it was 15.6% very good category, and in cycle III there was 6.3% sufficient category, 65.6% in good category and 28.1% very good category. (2) learning completeness in the knowledge assessment cycle I was 54.9% of students completed, cycle II was 78.9% of students were complete and in cycle III students completed 84.4% (3) learning completeness in the skills assessment cycle I was 43 .75% of students complete, cycle II of 71.9% of students complete and in cycle III of students complete of 81.25%. The data above it clearly shows that the social science technology model with a constructivist approach that has been applied to heat and its transfer material can improve student learning outcomes in class VII-I School and Center – Janodaya Vidhyalaya, Madanapalli.